Hookworm infection is associated with decreased CD4+ T cell counts in HIV-infected adult Ugandans. - Bozena M Morawski; Miya Yunus; Emmanuel Kerukadho; Grace Turyasingura; Logose Barbra; Andrew Mijumbi Ojok; Andrew R DiNardo; Stefanie Sowinski; David R Boulware; Rojelio Mejia (Public Library of Science (PLoS), 2017)
Most studies evaluating epidemiologic relationships between helminths and HIV have been conducted in the pre-ART era, and evidence of the impact of helminth infections on HIV disease progression remains conflicting. Less is known about helminth infection and clinical outcomes in HIV-infected adults receiving antiretroviral therapy (ART). We sampled HIV-infected adults for eight gastrointestinal parasites and correlated parasitic infection with demographic predictors, and clinical and immunologic outcomes. Contrasting with previous studies, we measured parasitic infection with a quantitative, highly sensitive and specific polymerase chain reaction (PCR) method. This cohort study enrolled HIV-infected Ugandans from August-September 2013 in Mbale, Uganda and collected stool and blood samples at enrollment. Real-time PCR quantified stool: Ascaris lumbricoides, Ancylostoma duodenale, Necator americanus, Strongyloides stercoralis, Trichuris trichiura, Cryptosporidium spp., Entamoeba histolytica, and Giardia intestinalis infection. Generalized linear models assessed relationships between parasitic infection and clinical or demographic data. 35% of participants (71/202) tested positive for ≥1 helminth, mainly N. americanus (55/199, 28%), and 4.5% (9/202) were infected with ≥2 stool parasites. Participants with hookworm infection had lower average CD4+ cell counts (-94 cells/mcL, 95%CI: -141, -48 cells/mcL; p<0.001) after adjustment for sex, CD4+ nadir at clinic entry, and time on ART. The high prevalence of parasitic infection and correlation with decreased CD4+ concentrations highlight the need to re-examine the effects of invasive helminth co-infection in rural, HIV-infected populations in the era of widely available ART. Elucidating the relationship between hookworm infection and immune recovery could provide opportunities for health optimization, e.g. integrated deworming, in these vulnerable populations.